CONTINUING EDUCATION AND THE PROBLEM OF SUCCESSION - Arzu Karimova (Foundations and Trends in Modern Learning, 2023)
The concept of lifelong learning as a scientific theory appeared in the first half of the 20th century, associated with the expansion of education, and with it, in the early stages. Continuous education - as one of the main principles of state policy in the field of education, is the possibility of obtaining education at several levels based on existing educational standards, curricula and plans, ensuring interaction between different levels of education and its continuous continuation throughout a person's life. In the 60s and 70s of the last century, the idea of "continuous education" appeared as the main ideology in many countries of the world. At the same time, the emergence and development of the idea of "continuous education" was contrary to existing programs. The concept of "continuous education" began to take shape in the 70s. According to the type and content of education, a system was established under different names: "continuous education", "restorative education", "continuous education", etc. then the initial review was substantially completed, both materially and organizationally. In the 70s and 90s of the 20th century, local and foreign scientists paid attention to the issues of more precisely defining the main characteristics of continuous education: - goals; - concept; - functions; - principles; - integration; - calculation of main subsystems; - defining the features and functional goals of their interactions; - integral education system, etc.